Probiotics, Nuclear Receptor Signaling, and Anti-Inflammatory Pathways - Sonia S. Yoon; Jun Sun (Gastroenterology Research and Practice)
There is increased investigation of the human microbiome as it relates to health and disease. Dysbiosis is implicated in various clinical conditions including inflammatory bowel disease (IBD). Probiotics have been explored as a potential treatment for IBD and other diseases. The mechanism of action for probiotics has yet to be fully elucidated. This paper discusses novel mechanisms of action for probiotics involving anti-inflammatory signaling pathways. We highlight recent progress in probiotics and nuclear receptor signaling, such as peroxisome-proliferator-activated receptor gamma (PPARγ) and vitamin D receptor (VDR). We also discuss future areas of investigation.